On hypercomplex numbers with third-order $k$-Jacobsthal numbers - Morales, Gamaliel (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We introduce a new family of hypercomplex numbers by using third-order $k$-Jacobsthal numbers. These sequences are called the third-order $k$-Jacobsthal $2^{r}$-ions. We present some algebraic properties of the third order $k$-Jacobsthal $2^{r}$-ions, such as the recurrence relation, the Binet formula, generating function, exponential generation function, the d'Ocagne identity, and the Cassini identity. Further, we obtain the matrix representation of the third-order $k$-Jacobsthal $2^{r}$-ions.